Associations of walking and resistance training with chronic low back pain in older adults: A cross-sectional analysis of Korean National Health and Nutrition Examination Survey data. Issue 11 (18th March 2022) - Nah, Sangun; Park, Seong San; Choi, Sungwoo; Jang, Hae-Dong; Moon, Ji Eun; Han, Sangsoo
Abstract : Abstract: Physical activities, such as resistance training and walking, are known to be effective against chronic low back pain (CLBP). However, few studies have examined the associations of walking and resistance training with CLBP in the general older population. Therefore, this study analyzed these relationships in the older Korean population (aged ≥65 years), with the goal of determining which exercise is better for CLBP. This cross-sectional study analyzed Korean National Health and Nutrition Examination Survey data for the period 2012 to 2015. The Korean National Health and Nutrition Examination Survey, which provides representative data for the Korean population, uses a clustered, multistage, random sampling method with stratification based on geographic area, age, and sex. Three multiple logistic regression models were generated in this study to determine the associations of walking and resistance training with CLBP. A total of 5233 participants were enrolled, 3641 (69.6%) of whom were free from CLBP; the remaining 1592 (30.4%) had CLBP. 78.4% and 64.8% of the non-CLBP and CLBP group patients, respectively, walked at least once a week. Also, 23.5% and 11.6% of the participants in the non-CLBP and CLBP groups, respectively, engaged in resistance training at least once a week. In the multiple logistic regression analysis, which was adjusted for all potential confounders, walking was significantly associated with a lower risk of CLBP (1-2d/wk: odds ratio [OR] = 0.65, P = .002; 3-4d/wk: OR = 0.69, P = .004; ≥5 d/wk: OR = 0.57, P < .001). However, resistance training showed no association with the risk of CLBP. In this cross-sectional study, walking was associated with a lower risk of CLBP. In particular, walking >5days per week had the maximum benefit in a lower risk of CLBP. Therefore, clinicians can consider recommending walking to patients with CLBP for optimal pain improvement.